2016
DOI: 10.1017/s0272263116000322
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Role of L1 Spoken Language Skills on Initial L2 Sign Language Learning

Abstract: Understanding how language modality (i.e., signed vs. spoken) affects second language outcomes in hearing adults is important both theoretically and pedagogically, as it can determine the specificity of second language (L2) theory and inform how best to teach a language that uses a new modality. The present study investigated which cognitive-linguistic skills predict successful L2 sign language acquisition. A group (n = 25) of adult hearing L2 learners of American Sign Language underwent a cognitive-linguistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Analogous to the similarity effect in word learning, visually distinct signs were learned more rapidly than visually similar signs. Second, Williams, Darcy, and Newman (2016a) investigated the role that, among other factors, a phonological STM task, digit span, would play in the prediction of ASL vocabulary growth. A multiple linear regression analysis with ASL vocabulary growth as the outcome variable revealed that neither forward nor backward digit span were predictive.…”
Section: Perceptual-motor Processes In Phonological Stm and Sign Learmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to the similarity effect in word learning, visually distinct signs were learned more rapidly than visually similar signs. Second, Williams, Darcy, and Newman (2016a) investigated the role that, among other factors, a phonological STM task, digit span, would play in the prediction of ASL vocabulary growth. A multiple linear regression analysis with ASL vocabulary growth as the outcome variable revealed that neither forward nor backward digit span were predictive.…”
Section: Perceptual-motor Processes In Phonological Stm and Sign Learmentioning
confidence: 99%
“…A multiple linear regression analysis with ASL vocabulary growth as the outcome variable revealed that neither forward nor backward digit span were predictive. Williams et al (2016a) theorized that digit span was not predictive because in nonsigners, this task would not assess critical modality-specific, that is, perceptual-motor, processes. They cautioned, however, that due to the small sample size ( n = 25), their results might not generalize.…”
Section: Perceptual-motor Processes In Phonological Stm and Sign Learmentioning
confidence: 99%
“…To our knowledge, no study has investigated the relationship between fluid intelligence and sign learning in hearing individuals acquiring a sign language and only one study has investigated crystallized intelligence as a predictor. J. T. Williams et al (2016a)…”
Section: Crystallized and Fluid Intelligencementioning
confidence: 99%
“…Importantly, however, the vast majority of individual differences research on lexical learning in adults has been conducted with spoken languages (e.g., Hundal & Horn, 1977;Kyllonen, Tirre, & Christal, 1991;Underwood, Boruch, & Malmi, 1978) and has largely overlooked lexical learning in signed languages (cf., Martinez & Singleton, 2018;Stone, 2017; T. Williams, Darcy, & Newman, 2016a). As a consequence, we know very little about the cognitive factors engaged while learning signs and whether they are similar and relied upon to the same degree as those employed during word learning.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous to the similarity effect in word learning, visually distinct signs were learned more rapidly than visually similar signs. Second, Williams, Darcy, and Newman (2016a) investigated the role that, among other factors, a phonological STM task, digit span, would play in the prediction of ASL vocabulary growth. A multiple linear regression analysis with ASL vocabulary growth as the outcome variable revealed that neither forward nor backward digit span were predictive.…”
Section: Perceptual-motor Processes In Pstm and Sign Learningmentioning
confidence: 99%